A calculus problem by Hobart Pao

Calculus Level 3

Given z = x + y + x + y + x + z=\sqrt{x+\sqrt{y+\sqrt{x+\sqrt{y+\sqrt{x+\cdots }}}}} , if z x ( x , y , z ) = ( 2 , 2 , 2 ) \left.\dfrac{\partial z}{\partial x}\right|_{(x, y,z)=(2, 2,2)} can be represented in the form a b \dfrac{a}{b} , where a , b a, b are coprime positive integers, find a + b a+b .


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hobart Pao
Mar 3, 2017

Solution.

z 2 = x + y + x + y + . . . z^2 = x + \sqrt{y+\sqrt{x+\sqrt{y+...}}} z 2 x = y + x + y + . . . = y + z z^2 - x = \sqrt{y+\sqrt{x+\sqrt{y+...}}} = \sqrt{y+ z} z 4 + x 2 2 z 2 x = y + z z^4 + x^2 -2z^2 x = y +z 4 z 3 z x + 2 x 2 ( 2 z x z x + z 2 ) = z x 4z^3\dfrac{\partial z}{\partial x} + 2x - 2 \left( 2zx \dfrac{\partial z}{\partial x} + z^2 \right) = \dfrac{\partial z}{\partial x} ( 4 z 3 4 z x ) z x 2 z 2 + 2 x = z x (4z^3 - 4zx) \dfrac{\partial z}{\partial x} - 2z^2 + 2x = \dfrac{\partial z}{\partial x} z x = 2 z 2 + 2 x 1 4 z 3 + 4 z x \dfrac{\partial z}{\partial x} = \dfrac{-2z^2 + 2x }{1-4z^3 + 4zx}

At ( x , y , z ) = ( 2 , 2 , 2 ) (x, y, z)=(2,2,2) , we get 2 2 2 + 2 2 1 4 8 + 4 2 2 = 4 15 ; 4 + 15 = 19 \dfrac{-2 \cdot 2^2 + 2 \cdot 2}{1-4 \cdot 8 + 4 \cdot 2^2} = \dfrac{4}{15}; 4+15=\boxed{19}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...